KNOWLEDGE AUDIT: A BIBLIOMETRICS ANALYSIS - Nur Hazelen Mat Rusok; Hafizah Mat Nawi; Nur Shaliza Sapiai; Norhafizan Awang; Siti Aswani Mohd Ghazali; Nor Erlissa Abd Aziz (International Journal of Accounting, Finance and Business, 2023)
A knowledge audit is a crucial building block for developing a thorough management strategy. This study aims at finding out the trend of publications with primary concentration on the topic of knowledge audit which was found yet to be conducted by any study to this day. This study employed the bibliometric analysis to analyse 166 indexed research from Scopus database from the year 1994 until 2023 based on defined search terms relating to knowledge audit. VOSviewer was employed to examine and generate a keyword map showing the connection between the topic and the co-occurrence network generated by keyword data. The study utilized Microsoft Excel 2016 to summarize the bibliometric data based on the parameters which include number of publications, subject areas and country contributions. The findings revealed that that researches on knowledge audit have been productively conducted throughout the years; 1994 to 2023 based on the bibliometric data of the defined parameters. The numbers of publication fluctuated throughout the period with 2018 witnessing the highest number of publication with 18 documents. In terms of the author, Gourova E. published the most numbers of article with 9 publications, and Lee W.B was the most cited authors with 120 citations recorded. As for document by affiliation, the University of St. Sofia Kliment Ohridski was ranked first with 9 published documents, while in terms of country, the United Kingdom was found to produce 25 knowledge audit documents. The United Kingdom again came first in terms of most numbers of citations and link strength with 25 and 337 respectively. For types of document, articles recorded the highest percentage compared to others with 48.0% or 73 documents. In terms of subject area, the highest percentage were recorded by computer science with 65 documents, and in terms of funding sponsors, Hong Kong Polytechnic University has the most documentation with 2 documents. The study has widened the area of study in knowledge audit despite being considerably broad in the study areas under the general keyword of knowledge audit.